Cytokinin activity of N6-benzyladenine derivatives assayed by interaction with the receptors in planta, in vitro, and in silico. (May 2018) - Savelieva, Ekaterina M.; Oslovsky, Vladimir E.; Karlov, Dmitry S.; Kurochkin, Nikolay N.; Getman, Irina A.; Lomin, Sergey N.; Sidorov, Georgy V.; Mikhailov, Sergey N.; Osolodkin, Dmitry I.; Romanov, Georgy A.
Abstract: Biological effects of hormones in both plants and animals are based on high-affinity interaction with cognate receptors resulting in their activation. The signal of cytokinins, classical plant hormones, is perceived in Arabidopsis by three homologous membrane receptors: AHK2, AHK3, and CRE1/AHK4. To study the cytokinin–receptor interaction, we used 25 derivatives of potent cytokinin N 6 -benzyladenine (BA) with substituents in the purine heterocycle and/or in the side chain. The study was focused primarily on individual cytokinin receptors from Arabidopsis . The main in planta assay system was based on Arabidopsis double mutants retaining only one isoform of cytokinin receptors and harboring cytokinin-sensitive reporter gene. Classical cytokinin biotest with Amaranthus seedlings was used as an additional biotest. In parallel, the binding of ligands to individual cytokinin receptors was assessed in the in vitro test system. Quantitative comparison of results of different assays confirmed the partial similarity of ligand-binding properties of receptor isoforms. Substituents at positions 8 and 9 of adenine moiety, elongated linker up to 4 methylene units, and replacement of N 6 by sulfur or oxygen have resulted in the suppression of cytokinin activity of the derivative toward all receptors. Introduction of a halogen into position 2 of adenine moiety, on the contrary, often increased the ligand activity, especially toward AHK3. Features both common and distinctive of cytokinin receptors in Arabidopsis and Amaranthus were revealed, highlighting species specificity of the cytokinin perception apparatus. Correlations between the extent to which a compound binds to a receptor in vitro and its ability to activate the same receptor in planta were evaluated for each AHK protein. Interaction patterns between individual receptors and ligands were rationalized by structure analysis and molecular docking in sensory modules of AHK receptors. The best correlation between docking scores and specific binding was observed for AHK3. In addition, receptor-specific ligands have been discovered with unique properties to predominantly activate or block distinct cytokinin receptors. These ligands are promising for practical application and as molecular tools in the study of the cytokinin perception by plant cells. Graphical abstract: Individual cytokinin receptors from Arabidopsis were assayed in planta, in vitro, and in silico with 25 different 6-benzyladenine derivatives, and new receptor-specific cytokinins were revealed.Image 1 Highlights: The cytokinin activity of 25 different 6-benzyladenine derivatives was assessed. Ligand preferences of individual cytokinin receptors from Arabidopsis were compared. New cytokinins active with distinct receptors were revealed. Cytokinin–receptor interaction was rationalized by molecular docking.